2022
DOI: 10.3390/sym14020192
|View full text |Cite
|
Sign up to set email alerts
|

Solving the Economic Growth Acceleration Model with Memory Effects: An Application of Combined Theorem of Adomian Decomposition Methods and Kashuri–Fundo Transformation Methods

Abstract: The primary purpose of this study is to solve the economic growth acceleration model with memory effects for the quadratic cost function (Riccati fractional differential equation), using Combined Theorem of Adomian Polynomial Decomposition and Kashuri–Fundo Transformation methods. The economic growth model (EGM) with memory effects for the quadratic cost function is analysed by modifying the linear fractional differential equation. The study's significant contribution is to develop a linear cost function in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…There are many different studies in the literature that reveal the accuracy of these statements [11][12][13][14][15][16][17][18][19][20][21]. There are many studies that show that it gives effective results when used by blending with different methods to reach solutions of nonlinear and fractional differential equations [22][23][24][25][26][27][28][29][30][31][32]. In this study, we demonstrate that the Kashuri Fundo transform, based on Newton's cooling law, which is modeled with first-order differential equations, is an effective, reliable and time-saving method for reaching solutions of first-order differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…There are many different studies in the literature that reveal the accuracy of these statements [11][12][13][14][15][16][17][18][19][20][21]. There are many studies that show that it gives effective results when used by blending with different methods to reach solutions of nonlinear and fractional differential equations [22][23][24][25][26][27][28][29][30][31][32]. In this study, we demonstrate that the Kashuri Fundo transform, based on Newton's cooling law, which is modeled with first-order differential equations, is an effective, reliable and time-saving method for reaching solutions of first-order differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…Kashuri Fundo transform was introduced to the literature by Kashuri and Fundo with the statement that various properties can be found easily due to its deep connection with Laplace transform [2]. In later processes, many researchers, including Kashuri and Fundo, worked on different applications [6][7][8][9][10][11][12][13][14][15][16] of this transform. Helmi et al [17], Singh [18], Dhange [19], and Güngör [20] investigated various applications of Kashuri Fundo transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Their significant contribution was to develop a linear cost function in the EGM for a quadratic non-linear cost function and determine the specific conditions of the Riccati fractional differential equations (RFDEs) in the EGM with memory effects. The results given in [3] showed that RFDEs in the EGM involving the memory effect have a solution and singularity. Additionally, the paper presented a comparison of exact solutions using Lie symmetry and a combined theorem of Adomian polynomial decomposition and Kashuri-Fundo transformation methods.…”
mentioning
confidence: 97%
“…Several examples were also given, including special functions, such as Bessel, Struve, Lommel, and q-Bessel functions. Johansyah et al [3] solved the economic growth acceleration model with memory effects for the quadratic cost function (Riccati fractional differential equation), using a combined theorem of Adomian polynomial decomposition and Kashuri-Fundo transformation methods. They analysed the economic growth model (EGM) with memory effects for the quadratic cost function by modifying the linear fractional differential equation.…”
mentioning
confidence: 99%